THE ROLE OF CUSTOMER SATISFACTION IN MEDIATING THE INFLUENCE OF RELATIONSHIP MARKETING ON CUSTOMER LOYALTY(Study on Dentino Dental Care Bali Patients) - I Nyoman Dyo Sucahya Permana; I Made Wardana (Adisam Publisher, 2024)
In addition to taking care of their teeth's health, people nowadays also seek dental care to enhance the aesthetics of their smiles with procedures like veneers, whitening, and dental jewellery. With this potential, extensive business opportunities in the health sector are created. This research was conducted at Dentino Dental Care located in Sukawati, Gianyar. The aim of this research is to test and explain the role of customer satisfaction in mediating the influence of relationship marketing on customer loyalty in Dentino Dental Care patients. The sample in this study was 100 respondents. Data collection was carried out by distributing questionnaires via Google Form. The collected data was analyzed using the classical assumption test, path analysis techniques, Sobel test and VAF test. The study's findings demonstrate that relationship marketing influences patient loyalty in a positive and significant way, as well as how customer satisfaction influences patient loyalty in a positive and significant way. Additionally, patient satisfaction can partially mediate the relationship marketing's effect on patient loyalty. Dentino Dental Care The implications of this research can be material for consideration and input for Dentino Dental Care in maintaining customer loyalty by considering relationship marketing and customer satisfaction variables.